Collaborative dialogue between Thai EFL learners during self-access computer activities - Kim McDonough (2018)
Previous studies have shown that second language (L2) learners use language to reflect on language form when they carry out collaborative classroom-based activities, and that they generally remember the language forms that they had discussed. The current study similarly investigated whether learners reflect on and remember language forms, but focused on learners' interaction during self-access computer activities. The language-related episodes (LREs) that occurred when Thai learners of English as a foreign language (EFL) (n = 48) carried out computer activities in a self-access environment were examined, and tailor-made tests that targeted the linguistic information discussed in those LREs were administered. The results indicated that the learners' LREs involved lexical items more often than grammatical forms, and that they successfully resolved the majority of their LREs while they were collaborating. However, their test performance indicated that they only remembered less than half of the lexical items and one-third of the grammatical forms that they had discussed. Suggestions are offered for teachers and administers interested in integrating collaborative self-access computer activities into English L2 courses.